Constitutive modeling for cyclic responses of saturated soft clay under principal stress rotation induced by wave loads. (15th May 2022) - Du, Zibo; Qian, Jiangu; Shi, Zhenhao; Guo, Yuancheng; Huang, Maosong
Abstract: A bounding surface model is proposed to reproduce the cyclic responses of saturated soft clay under principal stress rotation induced by wave loads. While extensively reported in experimental studies, this particular type of clay response has not been adequately addressed by constitutive modeling. By incorporating the mapping rules of relocatable projection center into the bounding surface, the plastic effects under pure principal stress rotation can be established. To represent the non-coaxiality during pure principal stress rotation, the presented model employs a non-coaxial flow rule sharing the same directions with the non-coaxial stress rate. However, it has been modified to related to the coaxial strain rate and the current stress ratio. Besides, the anisotropic elasticity is introduced for simulating the effects on plastic accumulation behavior during principal stress rotation. The developed model is validated through pure principal stress rotation tests of Shanghai clay and Wenzhou clay. The comparisons show that the proposed model can reasonably reproduce cyclic responses of saturated soft clay under principal stress rotation induced by wave loads. Highlights: A constitutive model is developed to reproduce cyclic responses of natural soft clay under wave loads. Plastic effects induced by pure principal stress rotation can be modeled by relocatable mapping rule. Non-coaxial flow rule and anisotropic elasticity are main characteristics of cyclic responses under pure principal stress rotation.